Corporate Social Responsibility (CSR) Practice of Cellular Phone Companies in Bangladesh - Hoque, Sayema; Chowdhury, Tanzina (IIUC Studies, 2014)
Cellular phone companies have occupied a significant position in the economy of Bangladesh. It has become one of the most profitable sectors as well as a big contributor to the government exchequer of this country. A great deal of economic resources is being utilized in this particular industry. Being an integral part of the society the companies operating within this industry are supposed to contribute towards social welfare through performing corporate social responsibility (CSR). In this backdrop, this study attempts to provide an overview of the CSR practices of the cellular phone companies of Bangladesh with special reference to the nature and impact of those practices. Based on the information provided in the annual reports and websites of respective companies the study has reached a conclusion that all the cellular companies except Airtel are engaged in CSR practices of some sort or other such as education, empowerment & poverty alleviation, environment, health care and others. However, there is still room for expanding CSR related activities to gain the potential benefits. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20403 IIUC Studies Vol.8 December 2011: 59-80